An Experience of Public Dental Care during the COVID-19 Pandemic: Reflection and Analysis - Nemeth, Orsolya (Int J Environ Res Public Health, 2021)
Since its emergence in China, the COVID-19 pandemic has become the number 1 health challenge in the world with all affected countries trying to learn from each other’s experiences. When it comes to health services, dental care does not seem to be a priority area, despite the fact that it is among the highest risk medical specialisations in terms of spreading the infection. Using the Department of Community Dentistry of Semmelweis University as a case study, the objective of this paper is to introduce and analyze the system and organizational level measures, which have been implemented in dental care in Hungary during the first months of the COVID-19 outbreak. The system level measures to promote social distancing, to reduce the use of health services and to protect high risk health professionals, together with the deployment of protective equipment and the reorganization of patient pathways at the organizational level proved to be effective in keeping the outbreak in control. There are two, less frequently mentioned ingredients of successful coping with the COVID-19 challenge. First, mental health support is at least as important as physical protection. Second, most of the interventions do not require big financial investments, but behavioural change, which in turn requires leadership and change management skills.